2017
DOI: 10.1111/ijfs.13411
|View full text |Cite
|
Sign up to set email alerts
|

Application of high‐power ultrasounds during red wine vinification

Abstract: Wine colour is one of the main organoleptic characteristics influencing its quality. It is of special interest in red vinifications due to the economic resources that wineries have to invest for the extraction of the phenolic compounds responsible for wine colour, compounds that are mainly located inside the skin cell vacuoles, where the volatile compounds are also found. The transfer of phenolic compounds from grapes to must during vinification is closely related to the type of grapes and the winemaking techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…In addition, Bautista‐Ortín et al . () attempted to apply high‐power ultrasound technology to red wine vinification, which indicated that ultrasonic technology has the potential to be applied to the brewing of fruit wine because it can reduce the brewing cycle and output cost (Bautista‐Ortín et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 99%
“…In addition, Bautista‐Ortín et al . () attempted to apply high‐power ultrasound technology to red wine vinification, which indicated that ultrasonic technology has the potential to be applied to the brewing of fruit wine because it can reduce the brewing cycle and output cost (Bautista‐Ortín et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 99%
“…It is clear that the use of ultrasound attracts a lot of interest in the enological field, however [2] did a literature review where it can be seen that almost all the previous studies have been done with laboratory equipment. We could only find two studies where a medium-scale system, suitable for working in small wineries, were used [11,12]. Our previous studies [11] reported that the wines made with ultrasound-treated grapes showed differences with the control wine, especially regarding total phenol content and tannin content.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging technologies that showed the greatest potential for increasing the extraction of skin compounds and controlling indigenous microorganisms are as follows: high hydrostatic pressure (HHP) [4][5][6], ultra high pressure homogenization (UHPH) [7][8][9], pulsed electric fields (PEFs) [10][11][12][13][14][15], electron-beam irradiation (eBeam) [16][17][18], ultrasound (US) [15,[19][20], and pulsed light (PL) [21][22][23]. Most of these technologies are either approved or under evaluation as new enological practices in the International Organization of Vine and Wine (OIV) regulations [24][25][26].…”
Section: Emerging Non-thermal Technologies For Grape and Must Processingmentioning
confidence: 99%